Socio-Economic; Oil Palm Plantation Company, Productivity; Character Building Gender. - Heriberta, Heriberta; Sartika, Delita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to: 1) Analyze the socio-economic conditions of freelancers in sustainable oil palm plantation companies based on labor productivity and gender inequality, and 2) Analyze how labor productivity and gender inequality affect the socio-economic perspectives of sustainable oil palm plantation companies in West Tanjung Jabung Regency. The research method used is a qualitative approach from a socio-economic perspective to obtain a more complete explanation of the quantitative results. This study also uses a quantitative approach, namely, multiple regression with a sample of 138 workers. The location of the research is an oil palm plantation company in West Tanjung Jabung Regency. The results of the analysis show that working hours have a significant and negative influence on the income of freelancers in palm oil companies. Meanwhile, the choice of the number of hours worked has no significant influence and has a negative value on income. On the other hand, crop yields have a positive and significant influence on the income of freelancers in palm oil companies in West Tanjung Jabung Regency.